1968
DOI: 10.1017/s0022112068000704
|View full text |Cite
|
Sign up to set email alerts
|

On slow transverse flow past obstacles in a rapidly rotating fluid

Abstract: This paper describes an experimental and theoretical study of the complicated disturbance (Taylor column) due to the slow relative motion between a spherical, or short cylindrical, rigid object and an incompressible fluid of low viscosity in which the object is immersed, when the motion of the object is that of steady revolution with angular speed Ω rad/see about an axis (the Z-axis) whose perpendicular distance from the centre of the object,$\overline{R}$, is much greater than a typical linear dimension of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 12 publications
4
24
0
Order By: Relevance
“…In the view 'west' (top right), it is seen that the spirals tend to be roughly aligned along the axis of rotation. The departure of the spirals from the perfect alignment is consistent with the result of Hide, Ibbetson & Lighthill (1968) that the motion of a particle perpendicular to the axis of rotation produces a deflected Taylor column with the angle of deflection proportional to the Rossby number.…”
Section: Development Of the Plumesupporting
confidence: 85%
“…In the view 'west' (top right), it is seen that the spirals tend to be roughly aligned along the axis of rotation. The departure of the spirals from the perfect alignment is consistent with the result of Hide, Ibbetson & Lighthill (1968) that the motion of a particle perpendicular to the axis of rotation produces a deflected Taylor column with the angle of deflection proportional to the Rossby number.…”
Section: Development Of the Plumesupporting
confidence: 85%
“…These waves would have a wavelength U/f ϳ1 cm and would propagate a horizontal distance approximately equal to the depth of the fluid (e.g., Hide et al 1968). Because the fluid depth at the slope transition ranged from 0-15 cm, it is unlikely that these waves had a strong influence on the eddies formed far downstream of the slope transition.…”
Section: B Discussionmentioning
confidence: 99%
“…If N = 0, the branch cut of § 4 extends from −if to if , leaving no space for a pole on the imaginary axis between the origin and the inertial-wave branch point, so there is no longer a slow mode and we have the problem and result of Stewartson (1953). This latter solution is only a local solution and, as pointed out by Lighthill (Hide, Ibbetson & Lighthill 1968), at large heights the disturbance decomposes into an inertial wave field (Cheng & Johnson 1982). The strength of the slow mode depends on the abruptness of the initiation of the motion and it has been shown that for sufficiently slowly accelerated bodies the mode can be arbitrarily weak.…”
Section: Discussionmentioning
confidence: 92%